PENGARUH SENAM LANSIA TERHADAP TEKANAN DARAH PADA LANSIA DI POSYANDU LANSIA KELURAHAN SUKAMAKMUR KECAMATAN SIANTAR MARIHAT KOTA PEMATANG SIANTAR - Pinondang Hotria Siregar (LPPM Universitas Abdurrab, 2023)
Hypertension is one of the main risk factors for cardiovascular disease which is the main cause of death for people in the world. The purpose of this study was to determine the effect of elderly gymnastics on blood pressure in the elderly at the Elderly Posyandu, Sukamakmur Village, Siantar Marihat District, Pematang Siantar City in 2023. The method in this study used a pre-experimental quantitative research method with a one-group pretest-posttest design. The population in this study were all elderly people in the Sukamakmur Village, Siantar Marihat District, Pematang Siantar City, totaling 55 people. Sampling was carried out using the Non Probability Sampling method with the Purposive Sampling technique. The results of the statistical assessment of p = 0.000 means that there is a difference between the results of the pre-test and post-test. The value of p <0.05 has a significant effect of elderly exercise on blood pressure. With the effect of elderly exercise on reducing blood pressure in the elderly with hypertension, it is hoped that all health workers, especially nurses, can provide prevention and health promotion efforts in the form of counseling to the elderly through elderly exercise which is carried out 3 times a week and still carry out routine blood pressure checks. at the health service center.